The influence of meteorological variables on the incidence of arbovirus cases in the Municipality of Belém, State of Pará (PA), Brazil (Research, Society and Development, 2025)
Arboviruses such as dengue, chikungunya, and zika represent an important threat to public health, whose expansion of Aedes aegypti breeding sites is related to meteorological variables, favoring their transmission. Thus, this study aimed to analyze the influence of meteorological variables on the incidence of dengue, chikungunya, and zika in the municipality of Belém (PA), from 2020 to 2024. Secondary data were obtained from the Information System for Notifiable Diseases (SINAN) and the National Institute of Meteorology (INMET). Statistical analyses using simple linear regression assessed associations between meteorological variables and arbovirus incidence, with a 5% significance level (p